PEMETAAN POTENSI TANAMAN PORANG SEBAGAI KOMODITAS EKSPOR - Priyanto, Eko; Sukaryorini, Pancadewi; Prabowo, Budi (Berkala Ilmiah AGRIDEVINA, 2016)
Ngawi has considerable forest area, either owned forests Forestry and Plantation Agency and owned by Perum Perhutani. These forests, automatically have forest land area under tree stands quite spacious as well, and is very suitable for planting Porang. In the end it can be said the forest is a potential for mapping the potential for plants Porang empowered. Against the backdrop of these conditions, this study aims to: 1. Identify Potential Land Plants Porang, to identify the extent of land to potential mapping Porangplants. The technical potential mapping on the basis of the terms Porang grow crops, such as: the suitability and condition of land; setempatyang weather and climate is verysuitable for plant growth Porang. 2. Analyzing Potential Mapping Strategies Porang plants, based on the SWOT method, ie factor strengths, weaknesses, opportunities and threats. The final results of this research to empower potential mapping strategy Porang plant in the district of Ngawi results of this study ultimately expected to empower the economy and welfare of the Farmers Forest (Pesanggem) local.Keywords: Potential Mapping Porang Plant.